2017
DOI: 10.1186/s12879-017-2581-8
|View full text |Cite
|
Sign up to set email alerts
|

The association between HIV (treatment), pregnancy serum lipid concentrations and pregnancy outcomes: a systematic review

Abstract: BackgroundObserved adverse effects of antiretroviral therapy (ART) on the lipid profile could be of significance in pregnancy. This systematic review aims to summarize studies that investigated the association between HIV, ART and serum lipids during pregnancy and adverse pregnancy outcomes.MethodsA systematic search was conducted in five electronic databases to obtain articles that measured serum lipid concentrations or the incidence of dyslipidaemia in HIV-infected pregnant women. Included articles were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…Pregnant WWE on EI-AEDs may be at higher risk of dyslipidemia with studies from HIC suggesting an association with carbamazepine use [ 74 78 ]. Similarly, HAART has been implicated in dyslipidemia [ 79 81 ] during pregnancy, and especially and PI intake [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pregnant WWE on EI-AEDs may be at higher risk of dyslipidemia with studies from HIC suggesting an association with carbamazepine use [ 74 78 ]. Similarly, HAART has been implicated in dyslipidemia [ 79 81 ] during pregnancy, and especially and PI intake [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…hypertensive disorder should be combined with other maternal characteristics, medical and obstetric history when calculating an individualized adjusted risk for adverse pregnancy complications. It was found that, hypertensive disorder increases the risk for stillbirth, PE, SGA, GDM, iatrogenic PTB and elective CS and reduces the risk for LGA (31). A study done in a facility based setting in China predicted adverse birth outcomes in a similar manner, precisely still birth which, the risk decreased as gestational age increased for all women and for all subtypes of hypertensive disorder and it was similar in hypertensive and normo-tensive women younger than 20 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Прослеживается взаимосвязь между АРВТ (ингибирующей протеазы) и сахарным диабетом. АРВТ токсически воздействует на стенку артерии, изменяя структуру ее липидов [1,[22][23][24][25][26][27][28].…”
Section: осложнения антиретровирусной терапииunclassified